Design and Implementation of Safe Security System Using Multi-Factor Authentication: Facial Recognition, National ID Card and PIN - Syahri Muharom; Sigit Adhi Sulistianto; Riza Agung Firmansyah; Wahyu Setyo Pambudi; Muchammad Kurniawan (JiTEKH, 2026)
Traditional storage cabinets that rely on conventional locks and provide unrestricted access are highly vulnerable to theft. To safeguard documents and other valuable items from loss, an integrated security system is required to regulate and secure access to storage compartments. This study aims to develop a security system based on facial recognition, ID cards, and a keypad interface The Haar Cascade classifier combine with LPBH utilizing the OpenCV library is employed for facial identification by storing 30 photos per person in a designated folder, and subsequently comparing facial objects captured by a webcam against pre-stored and trained facial data in the database. The analysis indicates that the optimal detection range of the system is between 100 and 300 cm. In facial orientation testing, the best recognition performance is achieved at angles between 0° and 40°. Based on 20 experimental trials, the system demonstrates an average success rate of 80%. These results suggest that a facial‑recognition‑based security system utilizing the Haar Cascade approach is feasible for implementation as a protective mechanism for storage cabinets.